Every company needs a political strategy today : five principles will help business leaders take decisive action when fast-changing laws and regulations conflict with stakeholder values - Levin, Blair; Downes, Larry (MIT Sloan Management Review, 2022)
Legal decisions made at the state and federal levels on controversial social policies have a direct impact on business, particularly when such rulings conflict with stakeholder values. The authors provide examples that illustrate why companies need to be prepared to respond strategically to sudden public policy changes and political upheavals, and offer five principles to help leaders plan a course of action.